THE IMPACT OF COMPUTER ASSISTED LANGUAGE LEARNING (CALL) ON IMPROVING INTERMEDIATE EFL LEARNERS’ VOCABULARY LEARNING - Enayati, Fatemeh; Pourhosein Gilakjani, Abbas (Universitas Negeri Makassar, 2020)
Regarding the large amount of vocabulary that learners should learn and the limited amount of time available in the EFL classes, Computer Assisted Language Learning (CALL) is considered as an attractive option for learning. One specific benefit of using CALL vocabulary instruction is to provide systematic repetition of words, ensuring that learned words are not forgotten. The objective of current investigation is to examine the effect of CALL on Iranian intermediate learners? vocabulary learning. The researchers used Tell Me More (TEM) software for this objective. This investigation used Preliminary English Test (PET) as a standardized measurement to seek the level of the subjects in terms of language proficiency. Then, the researchers assigned the participants into two groups: experimental group and control group. Experimental group included 31 EFL students and control group involved 30 EFL students. 80 items were administered as pre-test to evaluate the participants? previous knowledge of English in respect to the vocabularies. The researchers taught the students of both groups for 12 sessions. The TEM software was used as treatment in experimental group and the control group received no treatment. The taught words were the same in both groups. After 12 sessions, the 65 items were administered as post-test in order to compare the results of the scores of two groups and decide about the effectiveness of the treatment. The data were analyzed through running the Independent sample t-test. The results of post-test showed that the participants of experimental group outperformed the control group and had positive attitudes towards CALL. The results of this study may be useful for EFL teachers, EFL learners, and syllabus designers.